Effect of Model Inside Outside Circle Assisted by Smart Media Card on Social Sciences Learning Activity and Results - Reti Hesti (PAEDAGOGIA, 2019)
This study aims to find out and analyze the influence of the inside outside circle model assisted with smart card media on the activities and results of social studies learning in class III students of Pamotan Elementary School 01. This type of research is quantitative research with a Quasi Experimental Design research design with the Pretest-Posttest Control Group design. The samples taken were 26 students of IIIA class and 24 students of class IIIB using the Nonprobability Sampling technique in the form of saturated sampling. Based on data analysis, the following results were obtained: the mean pretest of the control class 69 and the experimental class 70, and the mean posttest of the control class 83, and the experimental class 90. So the results of the t-test tthitung (2,252) ≥ t tab (1,676). Based on the results of the hypotheses conducted, it means that there is a significant influence on the learning model inside outside circle assisted by smart card media on the activities and learning outcomes of social studies in third grade students of SDN 01 Pamotan.